Urban Furniture in the Framework of Economic, Social, and Environmental Sustainability - Yasar, Dilek (Street Art & Urban Creativity, 2023)
Urban furniture plays an important role in the making of sustainable cities and the need to incorporate sustainability requirements into the manufacture of urban furniture has been a part of ongoing debate for the last few decades and numerous studies have been performed on sustainable urban furniture. Notwithstanding above, there is only a limited number of integrated studies that address urban furniture with all its aspects associated with sustainability. Whereas, urban sustainability is a doctrine which is practically concretized with economic, social, and environmental aspects thereof. Accordingly, the present study investigates the material, production, and design stages of urban furniture in social, economic, and environmental contexts, and suggest recommendations regarding the necessary qualities of sustainable urban furniture. These recommendations include utilization of natural and local materials in the design of urban furniture, re-usability of the material, easy supply opportunities, durability against external factors, accidents, and vandalism, compliance with manufacture standards, allowing local intervention in case of damage, use of environmentally friendly technologies in production and design, suitability for long-term use, compatibility of design with the identity of the urban space in which it is located, arrangement and positioning in a way that allows its users to establish social relations, accessibility, and ability to serve all members of the society as much as possible.